Dog man - Pilkey, Dav (New York : Scholastic Inc., 2016, 2016)
New from the creator of Captain Underpants, it's Dog Man, the crime-biting canine who is part dog, part man, and ALL HERO!George and Harold have created a new hero who digs into deception, claws after crooks, and rolls over robbers. When Greg the police dog and his cop companion are injured on the job, a life-saving surgery changes the course of history, and Dog Man is born. With the head of a dog and the body of
Picture stories
1
Keywords: Comic and Graphic Books; Humor (Fiction)